Risk of dementia and education levels: When to learn is healthier of that than we think - Barrera, María Laura de la; Donolo, Danilo; Rinaudo, María Cristina (Anales de Psicología / Annals of Psychology, 2010)
The present investigation has as objective to know the percent-ages of adults that manifest certain predisposition to suffer dementia frontotemporal (FTD) or Alzheimer’s disease (AD) for the value obtained in the coefficient VLOM (initials in English of the subtests of verbal fluency + language / orientation + remember differed) and if these values can vary in gender function, age and level of education. We leave of defin-ing what we consider as knowledge and training cognitive, subsequently we meditate about the concepts of reservation cognitive and plasticity neuronal, to show the discoveries in the field study through the instru-ment ACE (Addenbrooke’s Cognitive Examination) of Maturanath et al., (2000) in an adapted version. We work with 649 adult subjects of the city of Río Cuarto and region, Córdoba, Argentina. We carry out analysis squared Chi, differences of means and Anova to know if differences exist in the performance in the instrument for groups. The results manifest that significant differences don’t appear for gender, but if certain tendencies is evidenced by age and level of education.